PENGELOLAAN PEMBELAJARAN PKN DENGAN MENGGUNAKAN METODE PEMBERIAN TUGAS DI SMK - Wita Mahdalena (Manajer Pendididikan, 2016)
This research was conducted at SMK Negeri 2 Kota Bengkulu, the type of research that is Class Action Research. Subjects in this study were students of class XI TAV 1 totaling 26students. Data were collected using observation sheets and questionnaires. Based on the initial questionnaire conducted on 26 students there are 10 students (38.5%) who get a low learning outcomes and only four students (15.4%) which has good value and the average value obtained 64.3%. Then in the first cycle there are six students, or (23.1%) who received good value criteria with an average value of 65.2%. In the second cycle increased to 21 or (80.8%) on the criteria of creativity is good and the average value obtained 86.5%. At the end of the meeting the questionnaire, there are 3 students (11.5%) who received low learning outcomes and only 21 students (80.7%) who received study results tub and niai average gained 80.5%. Based on the research results from the first cycle and the second cycle, learning management by administrationtasks can enhance students' creativity.Keywords: creativity, task